Berit Olam - Linafelt, Tod (Berit Olam, 1999)
Title page -- Copyright -- Ruth -- Dedication -- Contents -- Acknowledgments -- Introduction -- 1. The Bond Between Ruth and Naomi -- 2. Finding Favor in Boaz's Field -- 3. An Ambiguous Encounter in the Night -- 4. Making it all Legal -- For Further Reading -- General Index -- Index of Scriptural References -- Esther -- Dedication -- Contents -- Acknowledgments -- Introduction -- 1. Beginning with the End of Vashti -- 2. Remembering to Forget: Esther 2:1-4 -- 3. New Family Dynamics: Esther 2:5-18 -- 4. Coup: Esther 2:19-23 -- 5. Politics of an Anti-Jew: Esther 3:1-15